Measuring the cost of U.S. housing policy - Richard Cóndor (Banco de México, 2019)
Unlike other developed countries, the U.S. has a high proportion of long-term fixed-rate mortgages (30 years). This is partly because the Government Sponsored Enterprises (GSE), which operate in the secondary mortgage market, reduce the interest rate of these contracts. This document measures the cost and studies the consequences of such policy. GSE's actions are modeled as an interest rate subsidy applied directly to 30-year mortgages, in the context of a general equilibrium model with two types of agents, housing and default. The cost of this policy is measured as the minimum subsidy that makes households choose 30-year fixed-rate contracts over one-year contracts, in equilibrium. The resulting subsidy is 36 basis points. Finally, I investigate how the results vary with the duration of the fixed-rate mortgage contract, and I find that mortgage terms under 30 years require smaller subsidies.
Keywords: G12; G15; F31; 330; mortgage contracts; housing policy